THE CONSTRUCTION OF PRODUCTIVE MAHAR CONCEPT IN THE LOCAL WISDOM OF LOMBOK TENGAH COMMUNITY AND ITS IMPLICATION FOR FAMILY RESILIENCE - Munawirsazali, Munawirsazali; Suparlan, Suparlan (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study explores the construction of the productive mahar (dowry) concept within the local wisdom of the Tanak Awu community in Central Lombok and its implications for family resilience. Using a literature review and thematic approach, the research finds that the community has a distinctive perspective on determining the form of dowry given by the prospective husband to his future wife. Unlike conventional dowry practices, the productive mahar is designed to provide long-term economic benefits, serving as an asset that strengthens the financial stability of the family. The study identifies three key implications of this practice: (1) Religious implications, where the mahar is perceived as a symbol of commitment and responsibility in accordance with Islamic teachings; (2) Socio-cultural implications, reinforcing traditional values and strengthening community bonds; and (3) Economic implications, where the productive mahar functions as an investment that supports sustainable livelihoods. By integrating these aspects, the productive mahar contributes to family resilience, ensuring economic security while preserving local traditions. This research highlights the importance of culturally embedded dowry practices in fostering sustainable family well-being and offers insights into alternative mahar models that can be adapted in broader socio-economic contexts.